1996
DOI: 10.1016/0378-4347(95)00432-7
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine methyltransferase: a review and a clinical pilot study

Abstract: Thiopurine methyltransferase (TPMT) is an important enzyme in the metabolism of 6-mercaptoptirine (6MP), which is used in the treat men t of acute lymphoblastic leukemia (ALL). TPMT catalyzes the formation of methylthioi nosine monophosphate (MetlMP), which is cytotoxic for cultured cell lines, and it plays a role in detoxification of 6MP, Population studies show a genetic polymorphism for TPMT with both high and low activity alleles. About 1 of 300 subjects is homozygous for the low activity. The function TPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…1, 2). TPMT ac tivities in peripheral mononuclear cells ranged from 4.6-16.1 IU/109 cells in the present group, demonstrating in termediate and high activity [25]. The genetic polymor phism of TPMT may be partially responsible for the interpatient variability.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…1, 2). TPMT ac tivities in peripheral mononuclear cells ranged from 4.6-16.1 IU/109 cells in the present group, demonstrating in termediate and high activity [25]. The genetic polymor phism of TPMT may be partially responsible for the interpatient variability.…”
Section: Discussionmentioning
confidence: 44%
“…The genetic polymor phism of TPMT may be partially responsible for the interpatient variability. We could not demonstrate a cor relation between TPMT activity and (methyl)thiopurines, because a high percentage of TPMT assays in mononuclear cells fail due to the lack of cells in leukopenic patients as well as other enzymes involved in thiopurine metabolism (Scheme 1) [25]. Measurement of TPMT in RBC would not be informative because RBC are transfused during the in duction and consolidation treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In an earlier study, 23 using a radiochemical TLC procedure, we could not measure pMNC TPMT activity in nine out of 36 cases because these patients were leucopenic and we were unable to collect the necessary 5610 6 cells for the assay. However, with the present HPLC -based method, we can perform the assays with only 2610 6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has recently been shown that uremia in renal transplant is a significant inducer of TPMT activity [26]. Only one study to date has addressed the issue of TMPT activity in healthy controls following the administration of 6-MP, and reported no induction of TPMT activity [32]. Finally, several pharmacologic studies, performed both in vitro and in vivo, have reported inhibition of this enzyme and an increase of 6-thioguanine nucleotides owing to administration of sulfasalazyne or 5-aminosalicylates, both drugs frequently prescribed in patients with IBD [10,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%